Production of agroindustrial ashes with pozzolanic activity via acid leaching, conjugated burning and ultrafine grinding - Cordeiro, Guilherme Chagas; Lemos, Mônica Nunes; Xavier, Kristian Vinco; Lima, Charles Prado Ferreira de (Ambiente Construído, 2020)
This paper aims to study the production and the physical and chemical characterization of rice husk, sugarcane bagasse, corn straw, and bamboo leaf ashes to use as pozzolans. The ash production steps basically consisted of raw material collection, chemical treatment by citric acid leaching, conjugated burning (thermal processing) and ultrafine grinding (mechanical processing) of the produced ashes. The results indicated that all ashes could be classified as pozzolanic additions based on specific standards. The high pozzolanicity of the ashes was confirmed by testing the electrical conductivity, mechanical performance index, and hydration kinetics of cement pastes by isothermal calorimetry. Therefore, the production processes used in this work were effective in producing highly reactive pozzolanic materials.